Bikeability: Assessing the Objectively Measured Environment in Relation to Recreation and Transportation Bicycling. Issue 8 (October 2020) - Porter, Anna K.; Kohl, Harold W.; Pérez, Adriana; Reininger, Belinda; Pettee Gabriel, Kelley; Salvo, Deborah
The objectives of this study were to examine the association between objectively measured environmental variables and transportation and recreation bicycling frequency, and to develop transportation and recreation bikeability indices. Exploratory factor analysis was used to identify the underlying essential structure of the environmental variables under consideration. Many environmental variables were found to be correlated with transportation bicycling frequency, but not recreation bicycling frequency. The final transportation bikeability index included the combined effect of bicycle lanes, residential density, population density, ozone level, distance to transit, parks, and tree canopy coverage, and was found to have a significant direct association with any past-year transportation bicycling (odds ratio [OR] = 1.42, 95% confidence interval [CI] = [1.35, 1.52]) and transportation bicycling frequency (incident rate ratio [IRR] = 1.14, 95% CI = [1.09, 1.19]). This work will help advance research on bicycling and public health by providing a tool that can be utilized to examine transportation bicycling and the objective environment in the context of the United States.